The presence of the notary public in the Board meetings and his certiication of corporate minutes. Regarding the amendment of article 170 of the General Corporations Law - Peró Mayandía, Mariano (2015)
Corporate bodies are essential for the development of companies activities, and their minutes provide a means of evidence and proof of the deliberations and resolutions adopted therein. In certain conlict situations, the presence of a notary public is required in the meetings in order to verify the legality and validity of the resolutions adopted. This is why the General Corporations Law provides for the possibility that the notary public witnesses the general shareholders meeting, but omits it in the case of the board of directors. In this context, the amendment of article 170 of the General Corporations Law expressly incorporates the possibility of counting with the presence of a notary public in the board of directors in order to certify the authenticity of the resolutions and implement immediately the decisions adopted by both corporate bodies.